FAKTOR PRIBADI, LINGKUNGAN, DAN SOSIOLOGI PADA TAHAP INISIASI PROSES KEWIRAUSAHAAN IKAN HIAS DI KOTA BEKASI - Setyawasih, Rianti (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2016)
This study aim to find out and analyzed the personal factors, environmental, and sociological influences the initiation stage (triggering event) of the entrepreneurial process of ornamental fish in Bekasi.  This research refers to a model developed by Moore (1986) which describes how the process of entrepreneurship that is formed in a model that consists of four factors (i.e. factors of personal, family, environmental and social organizations) to four stages (i.e. the stage of innovation, initiation, implementation, and growth). This model is used to examine the presence of entrepreneurial process in Bekasi as the largest exporter of ornamental fish town in Indonesia.  Primary data of this research is obtained through the survey/interview using a questionnaire to a number of entrepreneurial ornamental fish in the town of Bekasi and descriptive quantitative research methods, with the analysis of Structural Equation Modelling using SmartPLS software.  The results showed that the personal and environmental factors doesn?t effect on the performance of significant entrepreneurial ornamental fish at the stage of initiation, while the influential sociological factors positively and significantly to the performance of entrepreneurial. Indicator role models is set on internal factors of sociology. The performance of entrepreneurial ornamental fish in Bekasi at the stage of initiation is very determined to success if at the time started his business supported by the availability of adequate standard and means of financial support of others.